Catalyst-free and efficient fabrication of highly crystalline fluorinated covalent organic frameworks for selective guest adsorption. Issue 32 (29th July 2019) - Liao, Qiaobo; Ke, Can; Huang, Xin; Zhang, Guiyang; Zhang, Qi; Zhang, Zewei; Zhang, Yiying; Liu, Yunzhong; Ning, Fangyi; Xi, Kai
Abstract : A catalyst-free and efficient method is employed to fabricate highly crystalline fluorinated COFs, which exhibit excellent selective dye adsorption performance. Abstract : Conventional synthesis methods for imine-linked covalent organic frameworks (COFs) usually require long reaction times, tedious synthetic procedures, and indispensable catalysts, restraining the further implementation of COFs. To tackle these obstacles, we report the first catalyst-free and highly efficient fabrication method for two imine-linked COFs by virtue of rationally designed building blocks. The compound 2, 3, 5, 6-tetrafluoroterephthalaldehyde (TFTA) was shown to be an active aldehyde monomer for accelerating the reaction and improving the crystallinity as well as the porosity. Remarkably, highly crystalline fluorinated SCF-FCOF-1 with a surface area exceeding 1000 m 2 g −1 was formed within 1 hour, and COFs with surface areas as high as 2056 m 2 g −1 were obtained after 3 days, representing the highest BET surface area for a fluorinated porous organic material. Moreover, the resultant fluorinated SCF-FCOF-1 exhibited excellent selective sorption performance and good recyclability toward positively charged organic molecules, presumably due to the high surface area, crystallinity, hydrophobicity and electrostatic attraction between the fluorine atoms and guest molecules.